My Country and My People - Lin, Yutang, 1895-1976 (London Heinemann, 1962)
In this classic book Yutang Ling does a fantastic job of describing Chinese people, customs and culture in an understandable way for the Western reader. this book was the first of it's kind, Ling being a rarity as he was fluent in both English and Chinese, having been born in China but growing up in America. This extremely popular book will prove to be a fascinating read, and is highly recommended on the bookshelf of anyone with an interest in different cultures and societies.
Include Appendices and Index
Keywords: China -- Civilization -- National Characteristics, Chinese -- Chinois